Why Study Online in Upper Secondary School? Qualitative Analysis of Online Learning Experiences - Kokko, Tiina; Pesonen, Henri; Kontu, Elina; Pirttimaa, Raija (Human Technology, 2015)
In Finland, online learning has become more common in recent years. In this study, we examined why adult students chose to study online for upper secondary school. The research also focused on the support needed for learning from a special education perspective. Both qualitative and quantitative data were collected using an electronic questionnaire. In total, 58 students responded. Data were analyzed qualitatively using the content analysis technique. The findings indicate that the main reasons for online studies are similar in Finland to those found internationally: flexibility of timetables, the student's health condition, and family situations. The findings also indicate that a student's school history leads them to choose online studies. This history included a lack of support, health issues, bullying, and too large class size. Suggested future research and practical implications also are discussed.